The war in Ukraine: economic consequences for Europe and Southeast Asia - Pitakdumrongkit, Kaewkamol (2023)
The Russia-Ukraine war has affected the economies of Europe and Southeast Asia, but not to the same extent. For European countries, the impact has been harder, mainly because of their dependence on pipeline gas from Russia and rising prices on global grain markets. Russia, on the other hand, was hit by sanctions, but enjoyed a boom in exports and its military industry. For Southeast Asia, although there are pockets of vulnerability, the economic impact has been limited, mainly because there are few direct economic links with Russia and Ukraine. As the Ukraine war is far from over, there is a need for EU and ASEAN to step up collaboration to bolster their respective economic security and resilience.